Penerapan pendekatan lingkungan alam sekitar (PLAS) untuk meningkatkan aspek afektif siswa - Pratiwi, Ashri Tri; Andriana, Encep; Hendracipta, Nana (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This study sought to investigate the implementation and effectiveness of the Environmental Surrounding Approach (PLAS) in the IPAS learning subject for fifth-grade students at SD Negeri Gunung Picung 04. The research employed a quasi-experimental, non-equivalent control group design. A total of 60 students participated, divided equally into two groups: an experimental class (n=30) that received instruction using the PLAS method, and a control class (n=30) that did not. Data collection relied on non-test instruments, specifically pre- and post-intervention questionnaires (pre- and post-respond) and classroom observations. The analysis utilized both descriptive and inferential statistics. The findings indicated that the PLAS method significantly improved students' affective domain scores in the experimental group. Their average affective score increased from 58.06 (pre-intervention) to 70.5 (post-intervention), which was corroborated by observation data yielding an average score of 41.86. In contrast, students in the control group showed a smaller gain in their affective domain, with the average score rising from 60.13 (pre-intervention) to 65.26 (post-intervention), supported by an observation average of 47.6.